The effects of ageing on genomic stability, self-renewal and pluripotency of embryonic stem cells - Low, Kok Yao (2014)
Embryonic stem cells are pluripotent cells capable of indefinite self-renewal. Due to their ability to be maintained on culture indefinitely, they are previously thought to be immune to the effects of ageing. However, there are emerging evidences that suggest otherwise. As such, based on known effects of ageing in non-embryonic stem cells and reported observations in literature, we identified pluripotency, self-renewal capacity and genomic stability as possible properties that can be affected by ageing in embryonic stem cells. We compared reactive oxygen species levels, levels of double strand breaks using γ- H2AX, proliferation and population profile as well as pluripotent markers expression between young and old mouse embryonic stem cells obtained from serial passaging. Our results suggest that ageing did not affect pluripotency or reduce self-renewal capacity in mouse embryonic stem cells. Genomic instability was observed in old mouse embryonic stem cells due to increased levels of double strand breaks detected. However, elevated levels of double strand breaks were not caused by age-dependent accumulation of reactive oxygen species, a DNA damaging agents. Old mouse embryonic stem cells also remained proliferative and resistant to cellular senescence.